ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII MTSN 3 LIMA PULUH KOTA - Siti Maha Rani; M. Imamuddin; Yusnita Yusnita (KOLONI, 2022)
Mathematical communication ability is the most important thing to be developed by students. Mathematical communication is a way for students to solve mathematical problems either orally or in writing. The purpose of this study was to analyze the mathematical communication skills of class VIII students of MTsN 3 Fifty Kota which were still low. This type of research uses qualitative methods. The subjects used in this study were determined by purposive sampling method. The sample of this study was students of class VIII.5 at MTsN 3 Fifty Kota as many as 3 students, namely those who had high ability (NT), medium (RA) and low (RN) out of 34 students and 1 math teacher (Buk ITA) ). Data were obtained through student tests with 3 indicators, namely (1) Students were able to express everyday events in language and mathematical symbols in the material on relations and functions. (2) Students are able to describe ideas, situations or pictures in relation and function material. (3) Students are able to connect real objects, images into mathematical ideas on relationships and functions. By validating through interviews. An interview with one of the eighth grade mathematics teachers said that students' ability levels varied according to their efforts. There are students who are careless during class hours and there are those who have very low abilities in mathematics. But there are also those who have the ability. Students who have moderate abilities have not been able to answer all the questions because they forget and do not understand the material properly along with the answers from their mathematics teacher only due to a lack of practice in discussing these questions. Furthermore, students who have high abilities. Students who have high communication skills can answer all questions based on these 3 indicators without any doubts and internalize and repeat them at home so as to get satisfactory results on the results of learning mathematics, especially material on relationships and functions. Keyword: Mathematical Communication Skills, Relations and Functions